Legal Politics of Regional Autonomy: The Problems of Shifting the Emphasis of Regional Autonomy - Lule, Alwadud; Soleman, Irwan (Budapest International Research and Critics University, 2021)
Regional autonomy is a relevant concept in a unitary state as an effort to give control to the regions to regulate and manage their own household affairs. Prior to the enactment of Law No. 23 of 2014 concerning Regional Government, the focus of full autonomy was on the districts/cities. Regency/city regions exercise autonomy, are broad, real and responsible. However, after the revision of the regional government law, the shift in autonomy was evident with the arrangement that shifted some of the district/city authority to the province. Even if we look closely, the shift in the emphasis of autonomy is not only shifting from district/city local governments to provincial governments, but the central government has implicitly withdrawn this authority. The implication is that the nature of autonomy, which actually makes the regions free and independent in administering the government, actually has dialectic in a direction that can distort the nature of regional autonomy.